Analisis Kondisi Iklim dan Pemanfaatannya untuk Penetapan Musim Tanam di Daerah Batabual Kabupaten Buru - Jamadin Biloro; Jacob Richard Patty; Semuel Laimeheriwa (Fakultas Pertanian, Universitas Pattimura, 2021)
The determination of the growing season is closely related with the climate change that occurs in a region The study aims to determine the trend of changing the growing season in the Batabual Area, changes in the growing season that occur due to changes in rainfall, and alternative planting patterns in Batabual region based on changes in the growing season that occur. Data analysis consisted of (1) determining the climatic conditions of the region using the Algebraic average method from monthly rainfall data from the Buru meteorological climate station for the last 30 years 1991-2020 and (2) determining the planting season using the FAO method (1978). The results showed that based on average rainfall data, the growing season lasted for 10 months and 19 days (November to September 19 of the following year). However, if you use rainfall with a 75% chance of being exceeded, the growing season period only lasts for 8 months and 21 days (December – July 21 of the following year).